Brand loyalty and the moderating role of involvement: a strategic alliance perspective in indonesia airline industry - Pratama, Anggun; Halim, Rizal Edy (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This research topic is about the membership of Garuda Indonesia (the biggest airline in Indonesia) into SkyTeam airlines alliance. This study aims to examine the influence of strategic airline alliance on the brand loyalty of Garuda Indonesia’s passengers in Indonesia. This research will examinethe relationship between strategic airline alliance, brand equity, brand preference and brand loyalty with a moderation effect of involvement on the relationship between strategic airline alliance and brand equity, and the relationship between brand preferences and brand loyalty. In particular, for both low and high involvement passengers, the effect of global airline alliances on brand equity, and brand preference on brand loyalty will be also examined by using structural equation model and multi-group method analysis. Data for this research were collected from Garuda Indonesia consumers, specifically those who have flown with Garuda Indonesia. They were then analyzed using Structural Equation Modelingand multi-group analysis method. The result on total sample of this research showed that all independent variables have significant effect to all dependent variables. However, in multi-group analysis, for both low and high-involved passengers, brand equity did not affect brand loyalty. Meanwhile, in other multi group analyses, all groups showed an effect on the relationship.